PENERAPAN METODE JOYFUL LEARNING DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MAN 2 KOTA SUKABUMI - Amelia Putri; Siti Sahira; Siti Nurazizah Maulidi; Apriliyani; Nurwanti Arfah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the joyful learning method in improving students’ learning interest in Islamic Religious Education at MAN 2 Sukabumi City. The background of this research is the low level of students’ learning interest, which is reflected in passive participation and lack of enthusiasm during the learning process. This study uses a qualitative approach with a field research method. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers and students. The data analysis technique was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the joyful learning method can create a more interactive, enjoyable, and student-centered learning atmosphere. This condition has a positive impact on increasing students’ attention, activeness, enthusiasm, and involvement in the learning process. In addition, students become more confident and motivated in participating in classroom activities. Therefore, the joyful learning method can be considered an effective alternative learning strategy in improving students’ learning interest, especially in Islamic Religious Education subjects.